PENERAPAN MODEL KOOPERATIF TIPE NUMBERED HEADS TOGETHER (NHT) DALAM MENINGKATKAN MOTIVASI BELAJAR PESERTA DIDIK DI SD (LPPM Universitas Buana Perjungan Karawang, 2024)
This research is motivated by problems in class V SDN 4 Gununglipung, namely students lack motivation to learn, because in teacher learning they do not vary, this causes students to get bored easily when carrying out learning activities because learning activities are more teacher-centered. This study aims to increase students' learning motivation. The research subjects totaled 22 students. The data collection methods used in this study were in the form of documentaries, questionnaires and observations. The analysis technique used is qualitative and quantitative analysis. Based on the results of the study, it can be concluded that the application of the Numbered Heads Together (NHT) cooperative learning model can increase student learning motivation, as evidenced by the increase in the percentage of learning motivation questionnaire analysis scores, in the pre-cycle. of 50.54%, cycle I of 69.09% increased in cycle II to 76.40%.